Peace is Better Business, and Business Makes Better Peace: The Role of the Private Sector in Colombian Peace Processes - Angelika Rettberg (German Institute of Global and Area Studies (GIGA), 2013)
The involvement of business in peace negotiations and peacebuilding has become a standard concern for countries involved in transitions from armed conflict. This article sheds light on the recent history of the private sector's role in peace processes in Colombia - a country that has been engulfed by conflict for almost five decades. The present paper illustrates how business perceptions and behavior have evolved throughout various attempts at negotiating peace, revealing that both the perceived costs of conflict and the expected benefits of peace play a part in promoting business pro-peace activism. A focus on business preferences is important for scholarly and public policy purposes. In light of dwindling international cooperation resources, it is likely that the Colombian state and society (mainly wealthy taxpayers and the business community) will bear the brunt of Colombia's peacebuilding costs. Understanding when, how, and why crucial allies (and potential foes) of peace processes become mobilized is therefore crucial for analyzing the prospects of durable peace in the country.
Keywords: D22; D74; N96; 330; Colombia; private sector; armed conflict; peace process; peacebuilding